Clinicopathological profile of children evaluated for suspected tuberculosis in a rural medical college hospital - Kalyanaraman, Padma; S, Sumathi (Indian Journal of Child Health, 2019)
Background: Tuberculosis (TB) is a major public health problem all over the world and India accounts for nearly one-third of the world TB burden. Pediatric TB has been estimated to account for approximately 20–40% of the cases in India. However, the diagnosis of childhood TB remains a challenge and is a major cause of concern in the eradication of TB. Objectives: The objectives of this study were to study the various clinical features and laboratory parameters in children suspected to have TB and to find out the most useful parameter to diagnose TB in children. Materials and Methods: This was a retrospective cross-sectional study conducted in a rural medical college hospital during the year 2017. Children up to the age of 14 years with a clinical diagnosis of suspicious TB were included in the study and the confirmation of TB was evaluated. All demographic data, contact history, symptoms, clinical findings, and laboratory parameters were retrieved from the medical records department and analyzed. Results: A total of 102 children were included in the present study and the predominant age group affected was between 5 and 10 years (30.4%) with male predominance (55%). The predominant clinical presentation was cervical lymphadenopathy (n=46; 45%) followed by contact history of contact with TB (n=34; 33.3%). Among the investigations, Mantoux positivity was observed in six cases, granulomatous lymphadenitis in 10 cases, and one pleural fluid analysis showed evidence of TB. Of 102 cases, 14 cases were confirmed as TB and one as latent TB infection (LTBI). Among the confirmed cases, cytological study was useful for confirming TB in 71.4% of cases, Mantoux positivity for five cases of TB (35.7%), and one case of LTBI. Conclusion: Cervical adenitis and contact history were common among suspected TB children and lymph node cytological study followed by Mantoux test was the useful parameters for confirming TB.